Alcohol Craving: Measurement - สุขตระกูล, สุนิศา (Journal of The Royal Thai Army Nurses, 2018)
Development of the concept of alcohol craving lead to the development of measurement to assess alcohol craving. Craving is the main cause of dependence and alcohol relapse. The most effective way of assessing craving for alcohol is not only increase knowledge but also benefits for clinical treatment. With a variety of measurement is being developed, choosing appropriate measurement requires deep understanding of the measure, know the purpose of measurement, the right audience for using those measurement and the conditions of each measure must be related to the basic concepts of researcher and the purpose of that measurement.